Abdominal obesity and cardiometabolic risk markers : A comparative analysis of waist circumference, dual-energy X-ray absorptiometry, and magnetic resonance imaging techniques - Ruano, Giulianna Regeni; Nogueira, Guilherme Augusto; Dadson, Prince; Ferreira, Sandra R.G.; Sapienza, Marcelo Tatit; Velloso, Licio A.; Monfort-Pires, Milena (Elsevier, 2025)
Background and aims
This study compares three methods to determine central adiposity (waist circumference –WC - and visceral adipose tissue – VAT - estimated by dual-energy x-ray absorptiometry – DXA, and by magnetic resonance imaging - MRI) in their ability to predict increases in cardiometabolic risk (CMR) markers in young individuals. We examined their associations with CMR in 47 men and women aged 25–40.
Methods and results
VAT mass was assessed using DXA and MRI. Blood samples were analyzed for CMR markers. Associations between central adiposity measurements and CMR factors were analyzed using Spearman's correlation coefficient, and the ability of these three central adiposity measurements to detect increased CMR was compared using receiver operating characteristic (ROC) curves. Similar to what was observed for the MRI-DXA and VAT-DXA, WC showed strong correlations with LDL-c and triglycerides (TG) and an inverse correlation with HDL-c (rho = −0.657 MRI, rho = −0.628 DXA, and rho = −0.604 WC, p < 0.01). On the other hand, only MRI-VAT and WC were associated with insulin and HOMA-IR (rho = 0.341 MRI and rho = 0.421 WC, p < 0.01). Central adiposity measurements were negatively associated with cold-induced 18F-FDG uptake in subcutaneous adipose tissue and positively associated with VAT TG content. No significant differences were observed when comparing the three central adiposity measurements in ROC curve analysis, and all measurements could predict increases in CMR markers and the combined CMR index.
Conclusions
This study reinforces the importance of using WC to assess increases in CMR markers among young adults. Given its practicality and efficacy, WC should be recommended in health centers to assess CMR risk.